Limited-Montage EEG as a Tool for the Detection of Nonconvulsive Seizures. Issue 1 (January 2022) - Swingle, Nicholas; Vuppala, Aditya; Datta, Proleta; Pedavally, Swetha; Swaminathan, Arun; Kedar, Sachin; Samson, Kaeli K.; Wichman, Christopher S.; Myers, Jacob; Taraschenko, Olga
Abstract : Purpose: Prefabricated arrays with a limited number of electrodes offer an opportunity to hasten the diagnosis of seizures; however, their accuracy to detect seizures is unknown. We examined the utility of two limited-montage EEG setups for the detection of nonconvulsive seizures. Methods: Thirty previously interpreted EEG segments with nonconvulsive seizures from 30 patients and 60 segments with background slowing or normal EEG from 60 patients were rendered in a bipolar "double banana" montage, a double distance "neonatal" montage, and a circumferential "hatband" montage. Experts reviewed 60 to 180 seconds long segments to determine whether seizures were present and if the EEG data provided were sufficient to make a decision on escalation of clinical care by ordering an additional EEG or prescribing anticonvulsants. The periodic patterns on the ictal-interictal continuum were specifically excluded for this analysis to keep the focus on definite electrographic seizures. Results: The sensitivities for seizure of the neonatal and hatband montages were 0.96 and 0.84, respectively, when compared with full montage EEG, whereas the specificities were 0.94 and 0.98, respectively. Appropriate escalation of care was suggested for 96% and 92% of occurrences of seizure patterns in neonatal and hatband montages, respectively. When compared with clinical EEG, the sensitivities of the neonatal and hatband montages for seizure diagnosis were 0.85 and 0.69, respectively. Conclusions: Nonconvulsive seizures were detected with high accuracy using the limited electrode array configuration in the neonatal and hatband montages. The sensitivity of the neonatal montage EEG in detecting seizures was superior to that of a hatband montage. These findings suggest that in some patients with nonconvulsive seizures, limited-montage EEG may allow to differentiate ictal and slow patterns. Abstract : Supplemental Digital Content is Available in the Text.